The Role of the Rangkang Pustaka Reading House in Improving Cultural Literacy in Elementary School Age Children in North Aceh Regency - Muhammad Ichsan Abda (Literatify: Trends in Library Developments, 2023)
The Rangkang Pustaka Reading House is an educational activity for children in North Aceh which provides a frame/hut containing books like a library and is equipped with a learning place such as an open meeting hall which can be used for all youth activities that are positive for education and self-development . Therefore, reading houses and libraries play an important role in introducing reading and writing activities from an early age. The research method used is a qualitative approach carried out objectively in the field. The types of data sources used in this research are primary and secondary data sources. The results of the research show that there is quite high motivation and facilities in the form of learning frames provided by the Rangkang Pustaka Reading House to improve literacy from an early age. This is proven by various activities carried out in terms of providing quality education-based learning and promoting lifelong learning in the form of fun, quality learning for free. However, children's awareness of participating in learning activities is still limited by time. Therefore, this has an impact on children's low literacy levels, especially in reading and writing activities. Literacy culture can develop well if children receive encouragement and motivation both from themselves and their parents, internal and external motivation.